Proteomic analysis of Bayvarol® resistance mechanisms in the honey bee parasite Varroa destructor. Issue 1 (1st January 2016) - Surlis, Carla; Carolan, James C.; Coffey, Mary F.; Kavanagh, Kevin
Abstract : The haemophagous mite, Varroa destuctor is one of the most dangerous threats to the Western honey bee, Apis mellifera. Varroa mites parasitize the larval and adult stages of the honey bee and can have devastating effects on the health of the individual bee and colony. In recent years, varroa have shown resistance to the pyrethroid group of insecticides, including Bayvarol ® which has flumethrin as the active ingredient. In the work presented here, changes in the expressed proteomes of mites, either sensitive or resistant to Bayvarol ® were observed using 2D-SDS-PAGE and shotgun label-free proteomics. A number of detoxification proteins (e.g., glutathione-s-transferase, flavin-containing monooxygenase) were present at higher levels in the resistant mites, as were some proton pumping proteins (e.g., Na+/K+ ATPase alpha and beta subunit, E1–E2 ATPase protein). A decrease in the abundance of 12 cuticle proteins in the resistant mites was observed indicating that alteration to cuticle structure could be a potential resistance mechanism. A number of structural proteins such as myosin and alpha tubulin were expressed at higher levels in the resistant mites, which could indicate a change to the intracellular structure of the cuticle barrier or a change in the cell shape/surface, rather than the addition of extra cuticle proteins. The results presented here indicate higher levels of protein associated with cellular detoxification in Bayvarol ® -resistant varroa mites.